A photocurable 3D printed part and its application in foaming material

By using photocuring 3D printing with low crosslinking density and low glass transition temperature, and introducing reversible covalent bonds under high temperature and high pressure conditions, the problem of difficult foaming of existing photocuring 3D printing materials is solved, and high performance preparation of multi-scale porous foaming materials is achieved.

CN116178633BActive Publication Date: 2025-03-21FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111433487.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-29
Publication Date
2025-03-21
Estimated Expiration
2041-11-29

AI Technical Summary

Technical Problem

The existing photocured 3D printing materials are difficult to use in the production of foamed materials due to their high cross-linking density and high glass transition temperature, and the interlayer bonding force is weak, which limits the mechanical properties of the materials.

Method used

Photocuring 3D printing is performed by using a photosensitive resin composition with a low crosslink density and a glass transition temperature below 30°C to form a polymer with a low crosslink density, and introduce reversible covalent bonds under high temperature and high pressure conditions to promote the dissolution and foaming of the high-pressure fluid.

Benefits of technology

The foamed materials that have achieved photocured 3D printing parts have good tensile properties, foaming properties, elasticity and surface smoothness, and the interlayer mechanical properties have been significantly improved, overcoming the shortcomings of traditional FDM-3D printing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116178633B_ABST
    Figure CN116178633B_ABST
Patent Text Reader

Abstract

The present invention provides a photocurable 3D printed part and its application in a foaming material. The photocurable 3D printed part of the present invention is an elastomer obtained by photocurable 3D printing, and the crosslinking density of the photocurable 3D printed part is 0.001 to 10 mmol / cm 3 , and the glass transition temperature is lower than 30°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to a photocurable 3D printed part and an application thereof in a foaming material. Background Art

[0002] Multiscale porous materials have been rapidly developed in different fields due to their advantages such as light weight, high load-bearing strength to mass ratio, low thermal conductivity, large impact energy dissipation, and good resilience. Such multiscale porous materials are widely used in cushions, membranes in separation processes, biological scaffolds, electromagnetic wave management, catalysis, and porous electrodes in the electronics and microelectronics industries. In recent years, porous materials prepared based on high-pressure fluid physical foaming technology have many advantages such as small pore size, high pore density, green environmental protection, and controllable foaming ratio. They are an important method for preparing microporous polymers. In order to make these polymer foam materials have a macroscopic three-dimensional structure, it is usually necessary to use a mold, which requires high mold opening costs and a long development cycle. It is limited by the limitations of mold opening and processing technology, and it is difficult to achieve the construction of complex porous structures.

[0003] 3D printing can quickly realize the construction of different complex structures and obtain materials with controllable shapes and adjustable properties. This technology has the characteristics of high degree of automation, high efficiency and personalized customization. At present, patent documents CN106493968A and CN110193931A disclose the production of foamed products based on nozzle-based fused deposition 3D printing technology (FDM-3D) combined with high-pressure fluid technology. FDM-3D printing technology is a processing method that uses thermoplastic polymer filaments as raw materials, melts and extrudes through a heated nozzle, and deposits molten filaments layer by layer to construct three-dimensional structural objects. This layer-by-layer deposition and solidification method does not form chemical crosslinks between layers, resulting in weak interlayer bonding and poor interlayer mechanical properties of foamed products, which limits practical applications.

[0004] In addition to FDM-3D printing technology, photocuring 3D printing technology is also a widely popular 3D printing technology. This technology has the advantages of short manufacturing cycle and high molding precision. Light is exposed on the surface of photosensitive resin according to the information of each layered section of the part, and the thin layer of resin in the irradiated area undergoes photopolymerization reaction and solidifies to form a thin layer. The workbench moves a certain distance of layer thickness, and new liquid resin is added to the gap to expose and solidify the next layer. Since the surface of the previous layer contains unreacted monomers, the resin of the new cured layer reacts with the resin of the previous layer during curing to form a chemical cross-linking network, which is firmly bonded to the previous layer, and this is repeated until the entire part is manufactured. Therefore, the mechanical properties between layers of the photocuring 3D printing process are far better than the processing technology of FDM-3D. Secondly, the printing resolution and surface fineness of the photocuring 3D printing process are higher than those of FDM-3D printing.

[0005] Generally speaking, photocurable 3D printing materials are mostly unsaturated resins. Under the irradiation of light of a certain wavelength, the photoinitiator absorbs light energy to form active free radicals or cations, which trigger the polymerization of resins containing multiple functional groups (mainly double bonds and epoxy groups) to form three-dimensional network polymers. However, due to the high cross-linking density, high glass transition temperature and small free volume space of the formed polymer, it is difficult for the high-pressure fluid used for foaming molding to dissolve into the polymer material to form a foaming material, so it is difficult to use photocurable 3D printing materials in the production of foaming materials. Summary of the invention

[0006] In order to improve the above technical problems, the present invention provides a photocurable 3D printed part, which is an elastomer obtained by photocurable 3D printing, and has a low crosslinking density and a glass transition temperature below 30° C. In addition, the present invention also provides a method for preparing a multi-scale porous foam material using the photocurable 3D printed part, and a multi-scale porous foam material obtained by the preparation method, and the foam material has good tensile properties, foaming properties, resilience and surface smoothness.

[0007] The present invention provides a photocurable 3D printed part, which is an elastomer obtained by photocurable 3D printing, and has a crosslinking density of 0.001 to 10 mmol / cm 3 , and the glass transition temperature is lower than 30°C.

[0008] According to an embodiment of the present invention, the photocurable 3D printed part of the present invention can be obtained from a photosensitive resin composition, specifically, by curing and molding the photosensitive resin composition using a photocurable 3D printing device. The photosensitive resin composition comprises a high molecular weight oligomer, a monomer, and a photoinitiator, wherein the number average molecular weight of the high molecular weight oligomer is 3500 to 100000 g / mol.

[0009] According to an embodiment of the present invention, reversible covalent bonds can be optionally introduced into the molecular chain segments of the high molecular weight oligomer. In the subsequent high temperature and high pressure foaming process for preparing the foaming material, the reversible covalent bonds are broken, so that the polymer network forms a thermoplastic network, which allows the high-pressure fluid to better dissolve into the polymer network, thereby achieving a better foaming effect.

[0010] According to an embodiment of the present invention, the reversible covalent bond may be a disulfide bond, a hindered amino bond, a boron oxygen bond, an imine bond, a Diels-Alder bond, a dynamic acylhydrazone bond, an oxime-carbamate bond or the like.

[0011] According to an embodiment of the present invention, the reversible covalent bond may be introduced into the high molecular weight oligomer by reacting a compound having the above-mentioned reversible covalent bond and having an amino group or a hydroxyl group at a molecular terminal with isocyanate.

[0012] According to an embodiment of the present invention, the number average molecular weight of the high molecular weight oligomer is preferably 6000 to 80000 g / mol, more preferably 8000 to 60000 g / mol.

[0013] In addition, in this invention, the number average molecular weight is measured using gel permeation chromatography (GPC).

[0014] According to the technical solution of the present invention, the high molecular weight oligomer can be one or more selected from polyurethane (meth) acrylate oligomers, polyurea (meth) acrylate oligomers, polyurea polyurethane (meth) acrylates, and vinyl terminated polydimethylsiloxanes.

[0015] According to the technical solution of the present invention, the polyurethane (meth) acrylate oligomer can be obtained by first reacting a polyol with an isocyanate, then adding a chain extender for the polyol, and then connecting an acrylic acid group or a methacrylate group to the terminal group. Alternatively, the polyurethane (meth) acrylate oligomer can be obtained by first reacting a polyol with an isocyanate, and then connecting an acrylic acid group or a methacrylate group to the terminal group. Alternatively, the polyurethane (meth) acrylate oligomer can be obtained by reacting a high molecular weight polyol with isocyanoethyl methacrylate.

[0016] According to the technical solution of the present invention, the polyurea (meth) acrylate can be obtained by first reacting a polyetheramine with isocyanic acid, then adding a polyamine chain extender, and then connecting an acrylic acid group or a methacrylate group to the terminal group. Alternatively, the polyurea (meth) acrylate can be obtained by first reacting a polyetheramine with isocyanic acid, and then connecting an acrylic acid group or a methacrylate group to the terminal group. Alternatively, the polyurea (meth) acrylate oligomer can be obtained by reacting a high molecular weight polyetheramine with isocyanoethyl methacrylate.

[0017] According to the technical solution of the present invention, the polyurea polyurethane (meth) acrylate oligomer refers to an oligomer containing a polyurethane structure and a polyurea structure, which is obtained by selecting at least one of a soft segment polyol and a polyetheramine, reacting with an isocyanate, adding at least one of a polyol or a polyamine chain extender, and then connecting an acrylic acid group or a methacrylate group to the terminal group.

[0018] According to the technical solution of the present invention, the isocyanate can be at least one selected from diphenylmethane diisocyanate, isocyanoethyl methacrylate, toluene diisocyanate, hydrogenated phenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, p-phenylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, and naphthalene diisocyanate.

[0019] According to an embodiment of the present invention, the soft segment polyol may be at least one selected from polyether polyol, polyester polyol, polyolefin polyol, and polydimethylsiloxane polyol.

[0020] According to an embodiment of the present invention, the polyether polyol may be at least one selected from polytetramethylene glycol, polypropylene glycol, a divalent or ternary copolymer polyether glycol formed by polytetramethylene glycol and propylene oxide and / or ethylene oxide, and polytrimethylene ether glycol.

[0021] According to an embodiment of the present invention, the polyester polyol may be at least one selected from polycaprolactone diol and polyethylene adipate diol.

[0022] According to an embodiment of the present invention, the chain extender may be selected from polyols, diamines, alcoholamines and the like.

[0023] According to an embodiment of the present invention, the polyol chain extender may be at least one selected from 1,4-butanediol, trimethylolpropane, glycerol, ethylene glycol, propylene glycol, diethylene glycol, neopentyl glycol, 1,4-cyclohexanediol, and hydrogenated bisphenol A.

[0024] According to an embodiment of the present invention, the diamine chain extender may be at least one selected from 3,5-dimethylthiotoluenediamine and 2,4-diamino-3,5-dimethylthiochlorobenzene.

[0025] According to an embodiment of the present invention, the monomer may be a monofunctional monomer or a low-viscosity multifunctional monomer, specifically, it may be at least one selected from cyclotrimethylolpropane methylal acrylate, ethoxyethoxyethyl acrylate, acryloylmorpholine, butyl acrylate, isobornyl acrylate, isobornyl methacrylate, 2-(tert-butylamino)ethyl methacrylate, tetrahydrofuran acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, lauryl acrylate, isooctyl acrylate, tripropylene glycol diacrylate, 3-ethoxylated trimethylolpropane triacrylate, trimethylolpropane triethoxy acrylate, ethoxylated pentaerythritol tetraacrylate, 1,6-hexanediol diacrylate, propoxylated neopentyl glycol diacrylate, bisphenol A diacrylate, and polyethylene glycol diacrylate.

[0026] According to an embodiment of the present invention, the monomer may also include a multifunctional mercapto compound, which is not particularly limited and may be selected from, for example, trimethylolpropane tris(3-mercaptopropionate), tetrakis(3-mercaptopropionic acid) pentaerythritol ester, (mercapto)propyl methylsiloxane, and tetrakis(3-mercaptobutyric acid) pentaerythritol ester.

[0027] According to an embodiment of the present invention, the photoinitiator is a free radical initiator, which can be selected from 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, 2,2-dimethoxy-1,2-diphenylethanone, 2-ethyloctyl-4-dimethylaminobenzoate, 4-dimethylamino-benzoic acid ethyl ester, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, camphorquinone, 4-dimethylaminobenzoic acid ethyl ester. At least one.

[0028] According to an embodiment of the present invention, the weight proportions of the components in the photosensitive resin composition are: 1 to 98 parts of high molecular weight oligomer, 1 to 98 parts of monomer, and 0.3 to 15 parts of photoinitiator.

[0029] According to an embodiment of the present invention, the photosensitive resin composition may further include a matting agent.

[0030] According to an embodiment of the present invention, the matting agent may be at least one selected from Sudan Red I, Sudan Red III, BASF Orizol Orange, and fluorescent whitening agent OB.

[0031] According to an embodiment of the present invention, the photosensitive resin composition may further include a leveling agent.

[0032] According to an embodiment of the present invention, the weight proportions of the components in the photosensitive resin composition are: 1 to 95 parts of high molecular weight oligomer, 1 to 98 parts of monomer, 0.3 to 15 parts of photoinitiator, 0.02 to 0.5 parts of matting agent, and 0.02 to 3 parts of leveling agent.

[0033] According to an embodiment of the present invention, the photosensitive resin composition is used in photocuring 3D printing, specifically, the photosensitive resin composition is used in photocuring stereolithography (SLA), digital projection processing (DLP) printing, desktop liquid crystal (LCD) printing, continuous liquid interface (CLIP) printing, two-photon 3D printer, and multi-material 3D printing.

[0034] According to an embodiment of the present invention, photocuring 3D printing can be performed under the following conditions: placing the photosensitive resin composition into a photocuring 3D printer, performing 3D printing under optional heating conditions, and then performing post-curing treatment to obtain a photocured 3D printed part.

[0035] According to an embodiment of the present invention, heating can be performed during the light-curing 3D printing process, and heating can reduce the viscosity of the resin composition so that printing can proceed more smoothly. The heating temperature can be 25°C to 80°C.

[0036] According to an embodiment of the present invention, during the light-curing 3D printing process, the post-curing treatment can be performed under an ultraviolet lamp.

[0037] According to an embodiment of the present invention, the crosslinking density of the photocurable 3D printed part of the present invention is 0.001 to 10 mmol / cm 3 , preferably 0.002 to 6 mmol / cm 3 , more preferably 0.004 to 2 mmol / cm 3 . By limiting the crosslinking density of the photocurable 3D printed part of the present invention to the above range, in the subsequent process of preparing the foaming material by placing it in a high-pressure container and injecting a high-pressure fluid, the high-pressure fluid can fully diffuse and dissolve in the elastomer material due to the low crosslinking density of the elastomer obtained by photocurable 3D printing, thereby forming a homogeneous system of polymer / gas; then, a supersaturated system is obtained by rapid pressure reduction or rapid temperature increase as a driving force, which triggers the nucleation of the homogeneous system; under the action of the driving force, the bubble nucleus grows, and a multi-scale porous material is obtained as the driving force disappears and the temperature of the polymer matrix decreases.

[0038] It should be noted that, in the present invention, the crosslinking density is measured by the equilibrium swelling method.

[0039] According to an embodiment of the present invention, the glass transition temperature of the photocurable 3D printed part of the present invention is lower than 30°C, preferably lower than 10°C, and more preferably lower than 0°C.

[0040] It should be noted that, in the present invention, the glass transition temperature is measured by differential scanning calorimetry (DSC) according to GB / T 19466.2-2004 standard.

[0041] In addition, according to the embodiment of the present invention, the Shore hardness of the photocurable 3D printed part of the present invention is 20A-50D, preferably 30A-80A, and more preferably 40A-70A.

[0042] It should be noted that, in the present invention, the Shore hardness is measured according to the American Society for Testing and Materials standard ASTM D1415 method.

[0043] In addition, according to the embodiment of the present invention, the tensile strength of the photocurable 3D printed part of the present invention is 0.5 to 30 MPa, preferably 2 to 20 MPa, and more preferably 2.5 to 10 MPa.

[0044] In addition, according to an embodiment of the present invention, the elongation at break of the photocurable 3D printed part of the present invention is 100% to 1200%, preferably 200% to 1000%.

[0045] It should be noted that, in the present invention, the tensile strength and elongation at break of the photocurable 3D printed parts before foaming are measured according to the method of ASTM D412 of the American Society for Experimental Materials.

[0046] In addition, according to the embodiment of the present invention, the resilience of the light-cured 3D printed part of the present invention is 20% to 80%, preferably 30% to 70%.

[0047] It should be noted that, in the present invention, the resilience is measured according to the method of ASTM D2632-2015 of the American Society for Testing and Materials.

[0048] The present invention also provides a method for preparing a multi-scale porous foam material using the photocurable 3D printed part, which comprises the following steps: placing the photocurable 3D printed part into a high-pressure container, injecting gas for high-pressure infiltration, and then quickly releasing the pressure to normal pressure, thereby obtaining a multi-scale porous foam material.

[0049] According to the present invention, "rapid pressure relief" means that the pressure on an object is relieved from high pressure to normal pressure or ambient pressure in a short time, and the average pressure relief rate of rapid pressure relief is greater than 2.5 MPa / s, for example, greater than 5 MPa / s, greater than 8 MPa / s, and greater than 9 MPa / s.

[0050] It should be noted that, in the present invention, "multi-scale porosity" means that for a printed part obtained by a photocuring 3D printing process, after being infiltrated and foamed by a high-pressure fluid, a micron-scale microporous structure is formed in the porous structure of the printed part itself.

[0051] According to an embodiment of the present invention, a photocurable 3D printed part is placed in a high-pressure container, and gas is injected. The gas diffuses fully in the printed part as a fluid under high pressure to form a homogeneous system. After a period of high-pressure infiltration, the pressure is quickly released to normal pressure, and the product is taken out to obtain a multi-scale porous structure product. In a preferred embodiment, the preparation of the product is carried out without a mold.

[0052] According to an embodiment of the present invention, the high pressure infiltration may be performed under heating, and the heating temperature is 10 to 180° C. higher than the glass transition temperature of the photocurable 3D printed part, preferably 50 to 150° C. higher.

[0053] According to an embodiment of the present invention, the high-pressure infiltration can also be performed without heating, and the light-cured 3D printed part is quickly depressurized, then immediately taken out and placed in hot water 20 to 200° C. higher than the glass transition temperature of the light-cured 3D printed part. In this way, the 3D printed part can be softened, making it easier for the gas to foam during the diffusion process.

[0054] According to an embodiment of the present invention, when the high-pressure infiltration is performed without heating, the light-cured 3D printed part can be quickly depressurized and then immediately taken out and heated in a microwave oven. In this way, after rapid heating in the microwave oven, the 3D printed part softens and can form larger pores.

[0055] According to an embodiment of the present invention, the gas may be at least one of carbon dioxide, nitrogen, methane, butane, methanol, ethanol and water (steam).

[0056] According to an embodiment of the present invention, after injecting gas into the high-pressure container, the pressure of the high-pressure impregnation may be 1 MPa to 40 MPa, preferably 2 MPa to 30 MPa, and more preferably 3 MPa to 25 MPa.

[0057] According to an embodiment of the present invention, after the gas is injected into the high-pressure container, the time of the high-pressure impregnation can be appropriately selected as needed, and can be 0.5 to 36 hours, preferably 1 to 24 hours, and more preferably 2 to 12 hours.

[0058] The present invention also provides a multi-scale porous foam material obtained by the preparation method of the multi-scale porous foam material.

[0059] According to an embodiment of the present invention, the tensile strength of the multi-scale porous foamed material of the present invention is 0.2 to 25 MPa, preferably 1 to 15 MPa, and more preferably 2 to 10 MPa.

[0060] According to an embodiment of the present invention, the elongation at break of the multi-scale porous foamed material of the present invention is 250% to 1500%, preferably 300% to 1000%.

[0061] It should be noted that, in the present invention, the tensile properties of the foamed sample are measured according to the method of GB / T6344-96.

[0062] According to an embodiment of the present invention, the foaming density of the multi-scale porous foam material of the present invention is 0.11 to 0.95 g / cm 3 , preferably 0.15 to 0.75 g / cm 3 , more preferably 0.2 to 0.5 g / cm 3 .

[0063] It should be noted that, in the present invention, the foaming density ρ f It is measured according to the American Society for Experimental Materials standard ASTMD792-2008. The foam density calculation formula is: ρ f =W1 / (W1+W2-W3)

[0064] Wherein, W1 is the mass of the foamed sample in the air, W2 is the weight of the metal ball that immerses the foamed sample in water, and W3 is the mass of the foamed sample in water.

[0065] According to an embodiment of the present invention, the foaming ratio of the multi-scale porous foam material of the present invention is 1.3-10, preferably 1.5-5.

[0066] It should be noted that, in the present invention, the expansion ratio is calculated according to the following formula: n = ρ p / ρ f Where n represents the foaming ratio of the printed sample, ρ p represents the density of the sample before foaming, ρ f Indicates the density of the sample after foaming.

[0067] In addition, according to the embodiment of the present invention, the multi-scale porous foam material of the present invention has good resilience. Specifically, the multi-scale porous foam material of the present invention has a resilience of 25% to 80%, preferably 30% to 70%.

[0068] Beneficial Effects

[0069] (1) The photosensitive resin composition containing high molecular weight oligomers provided by the present invention forms a polymer with low cross-linking density during the photocuring 3D printing process, which provides sufficient free volume space in the structure, so that the high-pressure fluid can fully diffuse in the printed polymer, and then form a cellular structure under rapid pressure reduction. The present invention overcomes the problem that traditional photocuring 3D printing materials cannot foam, and can realize the design and control of the hierarchical structure of the foaming material.

[0070] (2) The present invention uses photocuring 3D printing technology, with covalent chemical crosslinking between layers, strong interlayer bonding, and the mechanical properties of the products foamed with high-pressure fluid are far superior to those of FDM-3D printed thermoplastic materials. Photocuring 3D printing has high precision and good surface quality. The products foamed with high-pressure fluid only form a cellular structure inside, and the surface of the products can maintain high-precision details and smoothness.

[0071] (3) The present invention provides high molecular weight oligomers including polyurethane (meth) acrylate, polyurea (meth) acrylate, etc., which form elastomeric materials after printing and form multi-scale porous products under the action of high-pressure fluid, with the characteristics of low density and high rebound rate.

[0072] (4) The foaming device of the present invention is simple and only requires a sealed container. The photocurable 3D printed part can be placed in the container with or without heating, and then gas can be injected into the container. After the gas is allowed to penetrate the printed part for a certain period of time, the sample can be taken out to obtain a product with a multi-scale porous structure. The equipment is simple and easy to operate, and no additional chemical foaming agent is required, which is green and environmentally friendly.

[0073] (5) Although foaming is carried out in a foaming device, the shape of the finished product does not need to be defined by a mold, thereby greatly reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a schematic diagram of a process involved in Example 1 of the present invention;

[0075] Figure 2 are photos of the printed part prepared in Example 1 of the present invention before and after foaming;

[0076] Figure 3 is a scanning electron microscope image of a cross section of a printed part prepared in Example 1 of the present invention after foaming;

[0077] Figure 4 is a scanning electron microscope image of a cross section of a printed part prepared in Example 4 of the present invention after foaming;

[0078] Figure 5 is a glass transition temperature measurement curve of the DLP print of Example 1 of the present invention;

[0079] Figure 6 This is a photo of the actual product after foaming using FDM printing in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0080] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0081] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0082] Example 1

[0083] Preparation of multi-scale porous foam material 1

[0084] The specific steps for preparing the high molecular weight polyurea acrylate oligomer 1 are as follows:

[0085] 300g polyetheramine (molecular weight 4000g / mol), 15g hexamethylene diisocyanate and 10ml tetrahydrofuran were mixed, 0.03g dibutyltin dilaurate was added, and then the temperature was raised to 70°C for reaction for 5h, and then 3g of chain extender 3,5-dimethylthiotoluenediamine was added. After continuing the reaction for 1h, a small amount of oligomer was taken out, and the isocyanate content was measured by the method specified in HG / T2409-1992. When the theoretical value was reached, hydroxypropyl acrylate was added to react all isocyanate groups, and the reaction was continued at 70°C for 3h. The -NCO in the oligomer was tested by infrared to see if it was completely reacted. If the characteristic peak of -NCO at a wave number of 2260 disappeared, it meant that the hexamethylene diisocyanate had been completely reacted. The solvent tetrahydrofuran was removed by distillation under reduced pressure to obtain a high molecular weight polyurea acrylate oligomer 1 with a number average molecular weight of 35230g / mol.

[0086] Photocuring 3D printing: After high molecular weight polyurea acrylate oligomer 1 (60 g), 4-acryloylmorpholine (40 g), and 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide (2.5 g) were stirred at 60°C, and then stirred for 10 minutes with a planetary mixer to obtain a clear liquid. The obtained liquid was placed in a digital light processing (DLP) 3D printer and 3D printed at a temperature of 25°C to print a print with a frame structure, and then post-cured under ultraviolet light to obtain a photocuring 3D print 1, and its performance data are shown in Table 1.

[0087] Foaming molding: The above-mentioned photocurable 3D printed part 1 was placed in an autoclave, and CO2 gas was injected at a temperature of 60°C. The pressure was adjusted to 10 MPa, and the CO2 gas was allowed to completely immerse the printed part for 1 hour. Then the pressure was quickly released, and the average pressure release rate was 10 MPa / s. The product was taken out to obtain a multi-scale porous foam material 1, and its performance data are shown in Table 1.

[0088] Example 2

[0089] Preparation of multi-scale porous foam material 2

[0090] The specific steps for preparing high molecular weight polyurethane acrylate oligomer 2 are as follows:

[0091] 200g polycaprolactone diol (molecular weight 2000g / mol), 33.3g isophorone diisocyanate and 20ml tetrahydrofuran were mixed, 0.05g dibutyltin dilaurate was added, and then the temperature was raised to 50°C for reaction for 5h, and then 2g of chain extender propylene glycol was added. After continuing the reaction for 1h, a small amount of oligomer was taken out, and the isocyanate content was measured by the method specified in HG / T2409-1992. When the theoretical value was reached, hydroxypropyl acrylate was added to react all isocyanate groups, and the reaction was continued at 70°C for 3h. The -NCO in the oligomer was tested by infrared to see if it was completely reacted. If the characteristic peak of -NCO at a wave number of 2260 disappeared, it meant that the isophorone diisocyanate had been completely reacted. The solvent tetrahydrofuran was removed by reduced pressure distillation to obtain a high molecular weight polyurethane acrylate oligomer 2 with a number average molecular weight of 41870g / mol.

[0092] Photocuring 3D printing: After high molecular weight polyurethane acrylate oligomer 2 (50 g), lauryl acrylate (50 g), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (3 g) were stirred evenly at 60°C, the mixture was stirred for 5 min using a planetary mixer to obtain a clear liquid. The obtained liquid was placed in a digital light processing (DLP) 3D printer for 3D printing, and a print with a frame structure was printed. The print was then post-cured under an ultraviolet lamp to obtain a photocuring 3D print 2, and its performance data is shown in Table 1.

[0093] Foaming molding: The above-mentioned photocurable 3D printed part 2 was placed in an autoclave, and CO2 gas was injected at a temperature of 50°C. The pressure was adjusted to 5MPa, and the CO2 gas was allowed to completely immerse the printed part for 0.5h. Then the pressure was quickly released, and the average pressure release rate was 9.5MPa / s. The product was taken out to obtain a multi-scale porous foam material 2, and its performance data are shown in Table 1.

[0094] Example 3

[0095] Preparation of multi-scale porous foam material 3

[0096] The specific steps for preparing the high molecular weight polyurethane acrylate oligomer 3 are as follows:

[0097] 200g of polytrimethylene ether glycol (molecular weight 4000g / mol), 22.2g of isophorone diisocyanate and 50ml of tetrahydrofuran were mixed, 0.15g of dibutyltin dilaurate was added, and then the temperature was raised to 50°C for reaction for 5h, and then 4g of chain extender propylene glycol was added. After continuing the reaction for 1h, a small amount of oligomer was taken out, and the isocyanate content was measured by the method specified in HG / T2409-1992. When the theoretical value was reached, hydroxyethyl acrylate was added to react all the isocyanate groups, and the reaction was continued at 70°C for 3h. The -NCO in the oligomer was tested by infrared to see if it was completely reacted. If the characteristic peak of -NCO at a wave number of 2260 disappeared, it meant that the isophorone diisocyanate had been completely reacted. The solvent tetrahydrofuran was removed by reduced pressure distillation to obtain a high molecular weight polyurethane acrylate oligomer 3 with a number average molecular weight of 57440g / mol.

[0098] Photocuring 3D printing: After high molecular weight polyurethane acrylate oligomer 3 (80 g), acryloyl morpholine (40 g), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (3 g) were stirred evenly at 80°C, and then stirred with a planetary mixer for 5 minutes to obtain a clear liquid. The obtained liquid was placed in a stereolithography (SLA) 3D printer and 3D printed at a temperature of 60°C to print a print with a frame structure, and then post-cured under ultraviolet light, and then heated and annealed to obtain a photocuring 3D print 3, whose performance data are shown in Table 1.

[0099] Foaming molding: The above-mentioned photocurable 3D printed part 3 was placed in an autoclave, and CO2 gas was injected at a temperature of 110°C. The pressure was adjusted to 15 MPa, and the CO2 gas was allowed to completely immerse the printed part for 3 hours. Then the pressure was quickly released, and the average pressure release rate was 12 MPa / s. The product was taken out to obtain a multi-scale porous foam material 3, and its performance data are shown in Table 1.

[0100] Example 4

[0101] Preparation of multi-scale porous foam material 4

[0102] The specific steps for preparing high molecular weight polyurethane acrylate oligomer 4 are as follows:

[0103] 300g of polypropylene glycol (molecular weight of 3000g / mol), 24g of p-phenylene diisocyanate and 50ml of tetrahydrofuran were mixed, 0.05g of dibutyltin dilaurate was added, and then the temperature was raised to 50°C for reaction for 5h, and 3.6g of 2-hydroxyethyl disulfide was added. Then a small amount of oligomer was taken out, and the isocyanate content was measured by the method specified in HG / T2409-1992. When the theoretical value was reached, 2-(tert-butylamino)ethyl methacrylate was added to react all the isocyanate groups, and the reaction was continued at 70°C for 3h. The -NCO in the oligomer was tested by infrared to see if it was completely reacted. If the characteristic peak of -NCO at a wave number of 2260 disappeared, it meant that the p-phenylene diisocyanate had been completely reacted. The solvent tetrahydrofuran was removed by reduced pressure distillation to obtain a high molecular weight polyurethane acrylate oligomer 4 containing two reversible bonds, hindered amine and disulfide bonds, with a number average molecular weight of 6700g / mol.

[0104] Photocuring 3D printing: high molecular weight polyurethane acrylate oligomer 4 (80 g), acryloyl morpholine (40 g), isobornyl acrylate (10 g), ethyl 2,4,6-trimethylbenzoylphenylphosphonate (3 g) were stirred at 80°C and stirred for 5 min with a planetary mixer to obtain a clear liquid. The obtained liquid was placed in a digital light processing (DLP) 3D printer and 3D printed at a temperature of 45°C to print a print with a frame structure, and then post-cured under ultraviolet light to obtain a photocuring 3D print 4, the performance data of which are shown in Table 1.

[0105] Foaming molding: The above-mentioned photocurable 3D printed part 4 was placed in an autoclave, and CO2 gas was injected at a temperature of 100°C. The pressure was adjusted to 20 MPa, and the CO2 gas was allowed to completely immerse the printed part for 3 hours. Then the pressure was quickly released, and the average pressure release rate was 12 MPa / s. The product was taken out to obtain a multi-scale porous foam material 4, and its performance data are shown in Table 1.

[0106] Example 5

[0107] Preparation of multi-scale porous foam material 5

[0108] Vinyl-terminated polydimethylsiloxane (CAS No.: 68083-19-2, purchased from Sigma-Aldrich Company) with a molecular weight of 25000 g / mol was selected as the high molecular weight oligomer.

[0109] Photocuring 3D printing: Vinyl-terminated polydimethylsiloxane (100 g), (mercapto)propylmethylsiloxane (20 g), trimethylolpropane tris(3-mercaptopropionate) (15 g), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (3 g) were stirred at 50°C and stirred for 5 min with a planetary mixer to obtain a clear liquid. The obtained liquid was placed in a digital light processing (DLP) 3D printer and 3D printed at 60°C to print a print with a frame structure, and then post-cured under ultraviolet light to obtain a photocuring 3D print 5, the performance data of which are shown in Table 1.

[0110] Foaming molding: The above-mentioned photocurable 3D printed part 5 was placed in an autoclave, N2 gas was injected at a temperature of 50°C, the pressure was adjusted to 15MPa, the N2 gas was allowed to completely immerse the printed part for 5h, and then the pressure was quickly released, with an average pressure release rate of 9MPa / s. The product was taken out to obtain a multi-scale porous foam material 5, whose performance data are shown in Table 1.

[0111] Example 6

[0112] Preparation of multi-scale porous foam material 6

[0113] The specific steps for preparing high molecular weight polyurethane polyurea acrylate oligomer 6 are as follows:

[0114] 100g of polytetrahydrofuran diol (molecular weight of 2000g / mol), 22.2g of isophorone diisocyanate and 50ml of tetrahydrofuran were mixed, 0.05g of dibutyltin dilaurate was added, and then the temperature was raised to 70°C for reaction for 5h, and then 2.32g of dimethylglyoxime was added. After continuing the reaction for 1h, a small amount of oligomer was taken out, and the isocyanate content was measured by the method specified in HG / T2409-1992. When the theoretical value was reached, 2-(tert-butylamino) Ethyl methacrylate was used to react with all isocyanate groups, and the reaction was continued at 70°C for 3 hours. The -NCO in the oligomer was tested by infrared to see if it was completely reacted. If the characteristic peak of -NCO at a wave number of 2260 disappeared, it indicated that isophorone diisocyanate had been completely reacted. The solvent tetrahydrofuran was removed by vacuum distillation to obtain a high molecular weight polyurethane polyurea acrylate oligomer 6 containing two reversible bonds, oxime-urethane bond and hindered amine, with a number average molecular weight of 32150 g / mol.

[0115] Photocuring 3D printing: After high molecular weight polyurethane polyurea acrylate oligomer 6 (80 g), butyl acrylate (40 g), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (3 g) were stirred evenly at 80°C, and then stirred with a planetary mixer for 5 minutes to obtain a clear liquid. The obtained liquid was placed in a DLP-3D printer and 3D printed at a temperature of 30°C to print a print with a frame structure, and then post-irradiated under ultraviolet light to obtain a photocuring 3D print 6, the performance data of which are shown in Table 1.

[0116] Foaming molding: The above-mentioned photocurable 3D printed part 6 was placed in an autoclave, and CO2 gas was injected. The pressure was adjusted to 12 MPa, and the CO2 gas was allowed to completely immerse the printed part for 4 hours. Then the pressure was quickly released, and the average pressure release rate was 10 MPa / s. The product was taken out and placed in 100°C hot water for foaming to obtain a multi-scale porous foam material 6, whose performance data are shown in Table 1.

[0117] Comparative Example 1

[0118] Photocuring 3D printing: 80 g of bisphenol A propylene glycol dimethacrylate (number average molecular weight 512 g / mol), 17 g of isobornyl acrylate, and 3 g of ethyl 2,4,6-trimethylbenzoylphenylphosphonate were stirred at 80°C and stirred for 5 min with a planetary mixer to obtain a clear liquid. The obtained liquid was placed in a digital light processing (DLP) 3D printer and 3D printed at 60°C to print a print with a frame structure, which was then post-cured under ultraviolet light to obtain a comparative photocuring 3D print 1, and its performance data is shown in Table 1.

[0119] Foaming molding: The above-mentioned comparative light-cured 3D printed part 1 was placed in an autoclave, and CO2 gas was injected at a temperature of 120°C. The pressure was adjusted to 15MPa, and the CO2 gas was allowed to completely immerse the printed part for 3 hours. Then the pressure was quickly released, and the average pressure release rate was 12MPa / s. The product was taken out. Due to the high cross-linking density, it was difficult for CO2 to penetrate into the molecules, and foaming could not be achieved, and the original shape was maintained. Its performance data is shown in Table 1.

[0120] Comparative Example 2

[0121] FDM-3D printing: Thermoplastic polyurethane filament TPU, 85A, purchased from Shenzhen Guanghua Weiye Co., Ltd., was used. An FDM printer was used to print at a nozzle temperature of 250°C, a printing speed of 60 mm / s, and a filling rate of 50% to obtain FDM-3D printed part 1.

[0122] Foaming molding: The FDM-3D printed part 1 was placed in an autoclave, and CO2 gas was injected at a temperature of 80°C. The pressure was adjusted to 12 MPa, and the CO2 gas was allowed to completely immerse the printed part for 2 hours. Then the pressure was quickly released, and the average pressure release rate was 12 MPa / s. The product was taken out to obtain a comparative foaming material. Since thermoplastic materials were used for printing, the layers were physically bonded during the printing process, and the interlayer bonding force was weak. During the foaming and expansion process, cracks were easily produced, resulting in mechanical degradation. The performance data are shown in Table 1.

[0123] The performance test of the present invention is shown below:

[0124] Glass transition temperature: According to GB / T 19466.2-2004 standard, the glass transition temperature of the sample was tested by differential scanning calorimetry (DSC).

[0125] Crosslinking density: The crosslinking density was tested using the equilibrium swelling method.

[0126] Tensile strength / elongation at break of samples before foaming: The tensile properties and elongation at break of samples were tested according to ASTM D412, a standard of the American Society for Testing Materials.

[0127] Tensile strength / elongation at break of foamed samples: The tensile properties and elongation at break of the samples were measured according to the method of GB / T6344-96.

[0128] Foam density ρ f :The foaming density of the sample is tested according to the American Society for Experimental Materials standard ASTM D792-2008 f The calculation formula of foaming density is: ρ f =W1 / (W1+W2-W3)

[0129] Wherein, W1 is the mass of the foamed sample in the air, W2 is the weight of the metal ball that immerses the foamed sample in water, and W3 is the mass of the foamed sample in water.

[0130] Foaming ratio: Calculation formula: n = ρ p / ρ f Test. Where n represents the foaming ratio of the printed sample, ρ p represents the density of the sample before foaming, ρ f Indicates the density of the sample after foaming. When the foaming ratio is greater than 1, it means that it can be foamed, and the larger the value, the better the foaming performance; when the foaming ratio is 1, it means that it cannot be foamed.

[0131] Resilience: measured according to the method of ASTM D2632-2015.

[0132] Surface smoothness: The appearance of the foamed product was observed visually, and a foamed product with almost no cracks of 2 mm observed on the surface of the sample was evaluated as ○, and a foamed product with cracks of 2 mm was evaluated as ×.

[0133] Table 1

[0134]

[0135] It can be seen from the results in Table 1 above that the crosslinking density and glass transition temperature of the photocurable 3D printed elastomers in Examples 1 to 6 fall within the scope of the present invention, so that the foamed material obtained after foaming the photocurable 3D printed part has excellent tensile properties, foaming properties, resilience and surface smoothness.

[0136] Furthermore, by comparing Example 1 with Example 4, it can be seen that the introduction of reversible covalent bonds in high molecular weight oligomers can make the photocurable 3D printed parts form thermoplastic materials, and the gas is more likely to foam. From the electron microscope photos, it can be seen that larger spherical foaming cells ( Figure 4 and Figure 3 Comparison), thereby increasing the foaming ratio and the resilience.

[0137] In contrast, the photosensitive resin composition used in Comparative Example 1 contains a high molecular weight oligomer whose molecular weight does not fall within the range defined by the present invention, so that the photocured 3D printed part prepared from the photosensitive resin composition has a high glass transition temperature and a high crosslinking density and cannot be foamed.

[0138] Comparative Example 2 uses FDM-3D printing technology. Figure 6 It can be seen that there are obvious cracks between the layers of the foamed material. This is because: in the FDM-3D printing process, no chemical crosslinking is formed between the layers, resulting in weak interlayer bonding, which leads to a significant decrease in the mechanical properties of the foamed material. In contrast, the foamed material of the present invention adopts a light-curing 3D printing process, and there are covalent crosslinks between the layers. The layers will not expand and break during the foaming process. Therefore, the mechanical properties of the obtained print and its foamed material are far better than those of the FDM-3D printing process, and the surface fineness is also significantly higher than that of the FDM-3D printing process.

[0139] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A photocurable 3D printed part, which is an elastomer obtained by photocurable 3D printing, and the crosslinking density of the photocurable 3D printed part is 0.001 to 2 mmol / cm 3 , and the glass transition temperature is lower than 30°C, The tensile strength of the photocurable 3D printed part is 2-20 MPa, the elongation at break is 200%-1000%, and the resilience is 20%-70%; in, The photocurable 3D printed part is obtained by photocuring the photosensitive resin composition through 3D printing. The photosensitive resin composition comprises, by weight, 1 to 98 parts of a high molecular weight oligomer, 1 to 98 parts of a monomer, and 0.3 to 15 parts of a photoinitiator, wherein the number average molecular weight of the high molecular weight oligomer is 3500 to 100000 g / mol. The high molecular weight oligomer is selected from at least one of polyurethane (meth) acrylate oligomers, polyurea (meth) acrylate oligomers, polyurea polyurethane (meth) acrylates, and vinyl terminated polydimethylsiloxanes. A reversible covalent bond is optionally introduced into the molecular chain segment of the high molecular weight oligomer, and the reversible covalent bond is selected from at least one of a disulfide bond, a hindered urea bond, and an oxime-carbamate bond; The monomer is selected from cyclotrimethylolpropane formal acrylate, ethoxyethoxyethyl acrylate, acryloyl morpholine, butyl acrylate, isobornyl acrylate, isobornyl methacrylate, 2-(tert-butylamino)ethyl methacrylate, tetrahydrofuran acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, lauryl acrylate, isooctyl acrylate, tripropylene glycol diacrylate, 3-ethoxylated trimethylolpropane triacrylate, trimethylolpropane triethoxy acrylate, ethoxylated pentaerythritol tetraacrylate, 1,6-hexanediol diacrylate, propoxylated neopentyl glycol diacrylate, bisphenol A diacrylate, polyethylene glycol diacrylate, trimethylolpropane tris(3-mercaptopropionate), tetra(3-mercaptopropionic acid) pentaerythritol ester, (mercapto)propyl methylsiloxane, one or more thereof; The photoinitiator is selected from at least one of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, 2,2-dimethoxy-1,2-diphenylethanone, 2-ethyloctyl-4-dimethylaminobenzoate, 4-dimethylamino-benzoic acid ethyl ester, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, camphorquinone, and 4-dimethylaminobenzoic acid ethyl ester.

2. A method for preparing a multi-scale porous foam material using the photocurable 3D printed part according to claim 1, comprising the following steps: The photocurable 3D printed part according to claim 1 is placed in a high-pressure container, gas is injected, and infiltration is performed under a high pressure of 1 MPa to 40 MPa for 0.5 to 36 hours, and then the pressure is quickly released to normal pressure, thereby obtaining a multi-scale porous foam material. wherein the high pressure impregnation is performed with or without heating the high pressure container, In the case of heating, the heating temperature is 10 to 180°C higher than the glass transition temperature of the photocurable 3D printed part; Without heating, quickly release the pressure on the photocurable 3D printed part, take it out immediately, put it in hot water 20 to 200°C higher than the glass transition temperature of the photocurable 3D printed part, or heat it in a microwave oven.

3. The method according to claim 2, characterized in that The gas is selected from at least one of carbon dioxide, nitrogen, methane, butane, methanol gas, ethanol gas or water vapor.

4. The method according to claim 3, characterized in that The average pressure relief rate of the rapid pressure relief is greater than 5 MPa / s.

5. A multi-scale porous foam material obtained by the method according to any one of claims 2 to 4.

6. The multi-scale porous foam material according to claim 5, characterized in that: The multi-scale porous foam material has a tensile strength of 0.2 to 15 MPa and an elongation at break of 250% to 1000%.

7. The multi-scale porous foam material according to claim 5, characterized in that: The foaming density of the multi-scale porous foaming material is 0.11 to 0.95 g / cm 3 , The calculation formula of foaming density is: f =W1 / (W1+W2-W3), in, f It represents the foaming density, W1 is the mass of the foaming sample in the air, W2 is the weight of the metal ball that immerses the foaming sample in water, and W3 is the mass of the foaming sample in water.

8. The multi-scale porous foam material according to any one of claims 5 to 7, characterized in that: The foaming ratio of the multi-scale porous foam material is 1.3 to 10. The calculation formula of foaming ratio is: n= p / f , Where n represents the foaming ratio, p represents the density of the sample before foaming, f Indicates the density of the sample after foaming.

9. The multi-scale porous foam material according to any one of claims 5 to 7, characterized in that: The multi-scale porous foam material has a resilience of 25% to 80%.

Citation Information

Patent Citations

  • 3D printing method for high-performance foam shoe midsole

    CN110193931A

  • Resin foam and production method therefor

    CN103380170A

  • Method and apparatus for producing foamed product based on 3D printing

    CN106493968A

  • Photosensitive resin composition for photocuring 3D printing elastomer and preparation method thereof

    CN113105590A